Determinação das fontes alimentares de Anopheles aquasalis (Diptera: Culicidae) no Estado do Rio de Janeiro, Brasil, pelo teste de precipitina Blood-meal sources of Anopheles aquasalis (Diptera: Culicidae) in a South-eastern State of Brazil - Carmen Flores-Mendoza; Rodolfo A. Cunha; Dayse S. Rocha; Ricardo Lourenço- (Universidade de São Paulo, 1996)
Anopheles aquasalis é um mosquito ora encarado como antropofílico, ora como zoofílico ou eclético. Realizou-se estudo em Guapimirim, Estado do Rio de Janeiro, de maio a novembro de 1992, com o intuito de se verificar a fonte alimentar preferida desse anofelino através de teste imunológico de precipitina. De 1.366 fêmeas capturadas em abrigos naturais, 725 estavam ingurgitadas. O conteúdo digestivo de apenas 473 delas reagiu no teste de precipitina, sendo que em 75,3% dos casos foi identificada apenas uma fonte alimentar. Mais da metade dessas fêmeas havia se alimentado em boi (52,2%), enquanto poucas tinham sugado homem (1,1%). Por outro lado, 24,7% dos espécimes haviam se alimentado em mais de uma fonte sangüínea, principalmente boi e cavalo. Conclui-se que An. aquasalis é zoófilo nessa região do País, utilizando grande variedade de hospedeiros, porém preferindo se alimentar em animais de grande porte, especialmente o boi e cavalo. Anopheles aquasalis has shown local variations in blood-host preference in Brazil: it seems to be anthropophilic in the northeast and zoophilic or opportunistic in the Amazon and other regions. A study was carried out in Guapimirim county, State of Rio de Janeiro, from May to November 1992, for the purpose of identifying the blood meal source of this anopheline by capillary tube precipitin test. A total of 1,366 females were captured at natural resting-places, 725 of which were blood-fed. The gut content of 473 blood fed females reacted to the antisera used (human, cow, horse, pig, dog and chicken). The majority of the females ¾ 356 (75.3%) ¾ had blood from only one source. A substantial bovine preference was observed ¾ 52.2% had fed on cows, 29.8% on horses, 10.7% on pigs, 4.5% on chickens and 1.7% on dogs, but only few had fed on man (1.1%) and none on rats. On the other hand, 24.7% of the females had fed on more than one host, mainly on cows and horses. It was assumed that An. aquasalis is zoophilic in southeastern Brazil, feeding on a wide variety of animals, the cow being the primary host.